An improved security and message capacity using AES and Huffman coding on image steganography - Christy Atika Sari; Giovani Ardiansyah; De Rosal Ignatius Moses Setiadi; Eko Hari Rachmawanto (TELKOMNIKA (Telecommunication Computing Electronics and Control), 2019)
Information security is very important and has been widely implemented. Cryptography and steganography are two common methods that can be implemented to secure and conceal the information. In this research, the proposed AES algorithm for cryptography and DWT for steganography. However, in case of implementing DWT as steganography, there is a weakness which is a lower capacity. Based on DWT’s problem, proposed Huffman Coding to reduce the total of the message’s bit and increase the capacity. In the implementation, a message will be processed by using AES and compressed by using Huffman Coding then conceal in a cover using DWT. After doing several experiments using a 128x128 pixel message image and a 512x512 pixel of the cover image, achieved the average of MSE is 1.5676 and the average of PSNR result is above 40db which is 46.1878.